Development of Biology Practicum Guide to the Concept of the Digestive System in Developing Critical Thinking Students' - Mahrawi, Mahrawi; Mulyani, Diana; Rifqiawati, Ika; Hendriyani, Mila Ermila (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2022)
The aim of the study is to develop a biology practicum guide on the concept of the digestive system to develop students' critical thinking skills, to determine eligibility, and to determine student responses to the biology practicum guide. The research method is the research and development (R&D) method by using the Sugiyono model. The research was conducted in October 2021 at SMAN 2 Serang City. The population in the study was 10 students from class XI SMAN 2 at Serang City High School, school year 2021/2022. Data retrieval and collection techniques are carried out by spreading questionnaires and interviews, while data analysis techniques using guttman scales and likert scales are used to test the feasibility of the biology practical guides that have been created. The validity assessment from the material expert for the Biology Practicum Guide received a score of 85% and the score from the media expert got a score of 86%. Both values are very feasible in the category. The result of the students' response test was a 98.6% score, which was very feasible in the category. Thus, it can be concluded that the Biology Practicum Guide on the concept of the digestive system was very feasible to use to develop critical thinking skills in students.